2014
DOI: 10.1016/j.bpj.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Giant Unilamellar Vesicles Formed by Hybrid Films of Agarose and Lipids Display Altered Mechanical Properties

Abstract: Giant unilamellar vesicles (GUVs) are presumably the current most popular biomimetic membrane model. Preparation of GUVs in physiological conditions using the classical electroformation method is challenging. To circumvent these difficulties, a new method was recently reported, by which GUVs spontaneously swell from hybrid films of agarose and lipids. However, agarose is left encapsulated in the vesicles in different amounts. In this work, we thoroughly characterize the mechanical properties of these agarose-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 51 publications
5
85
0
Order By: Relevance
“…1B. Formation of liposomes from a film of ultra-low melting agarose hence led to giant liposomes with comparable, low-permeability-characteristics than liposomes prepared by other methods [55,58]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B. Formation of liposomes from a film of ultra-low melting agarose hence led to giant liposomes with comparable, low-permeability-characteristics than liposomes prepared by other methods [55,58]. …”
Section: Resultsmentioning
confidence: 99%
“…It remains to be seen if similar problems of leakiness will appear with reconstituted proteins other than P-gp or if this problem was protein-specific. Recently Lira et al reported that liposomes, which were also formed from films of agarose and were initially tight, became permeable to solutes upon transient pore formation by electroporation [58]. The authors explained this effect by trapping of agarose molecules in the membrane pores and a resulting attenuation of spontaneous pore closure.…”
Section: Discussionmentioning
confidence: 99%
“…This effect might be due to the improvement in the concentration of hydrophilic drugs in the inner water phase by the reversephase evaporation method, leading to the formation of large unilamellar vesicles. 35,36 In the uniform design, the EE was improved by increasing the phospholipid concentration in experimental formulations. Similar findings were previously reported by Shen et al and Fang et al 17,37 Glycerosomes are a kind of closed vesicles with a lipid bilayer structure similar to the biomembrane.…”
Section: Discussionmentioning
confidence: 99%
“…Hydration of a lipid film on a polymer cushion (of agarose [75] and of polyvinyl alcohol, PVA [76]) allows production of GUVs of virtually all membrane compositions in all kinds of aqueous solution. However, difficulties in detaching the formed GUVs from PVA films were reported [76], and GUVs grown on agarose films were shown to have a significant amount of encapsulated agarose that interfere with the vesicle mechanical properties [77].…”
Section: Drawbacks and Artifacts In Guv Experimentsmentioning
confidence: 99%